PENGARUH KNOWLEDGE MANAGEMENT, MOTIVASI KERJA, DAN QUALITY OF WORK LIFE (QWL) TERHADAP KINERJA KARYAWAN PADA PT. INDRABAKTI MUSTIKA DI KENDARI - Putri Bella Frajuli; Ibnu Hajar; Nursaban Rommy Suleman; Sabri Sabri (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2022)
This study aims: (1) to determine the effect of Knowledge Management, Motivation, and Quality  of Work Life on Employee Performance  of PT. Indrabakti Mustika In Kendari; (2) to determine the effect of Knowledge Management on Employee Performance  of PT.  Indrabakti  Mustika  In Kendari;  (3) to determine  the effect  of motivation on employee performance at PT. Indrabakti Mustika In Kendari; and (4) to determine  the  effect  of  Quality  of  Work  Life  on  Employee  Performance  of  PT. Indrabakti  Mustika  In  Kendari.  The  sampling  technique  used  in  this  study  was purposive sampling. In this study, samples were taken with the characteristics of male and  female  employees,  all  employees  with  permanent  employee  status  at  PT. Indrabakti  Mustika.  So  the  number  of samples  in this  study  were  50  permanent employees.The results showed that: (1) Knowledge Management, Motivation, and Quality of Work Life simultaneously had a positive and significant effect on the performance of PT. Indrabakti  Mustika  In  Kendari;  (2) Knowledge  Management,  partially  positive  and significant effect on Employee Performance of PT. Indrabakti Mustika In Kendari; (3) Motivation partially has a positive and significant effect on employee performance at PT. Indrabakti Mustika In Kendari; and (4) Quality of Work Life partially positive and significant effect on Employee Performance PT. Indrabakti Mustika In Kendari